Lymphocyte responses to phytohaemagglutinin in patients with asbestosis and pleural mesothelioma. - Haslam, P L (1978)
Quantitative impairment of lymphocyte responses to phytohaemagglutinin (PHA) has been demonstrated in six (21%) out of twenty-eight patients with asbestos-associated pulmonary fibrosis, in comparison with a group of unexposed normal controls. The impairment tended to occur in patients with fairly severe fibrosis, comparatively short duration of exposure to asbestos dust and with increases in serum immunoglobulin levels. One patient with asbestosis and an associated bronchial carcinoma also had depressed lymphocyte responses to PHA. These findings suggest a relationship between defective T-lymphocyte function and the fibrotic response in asbestosis. Whether it is also linked with the development of lung cancer, occurring either before or at a pre-clinical stage of tumour growth, and is of value in identifying patients especially at risk should now be explored in longitudinal studies. However, eight out of ten patients with asbestos-associated pleural mesothelioma and without lung fibrosis showed no evidence of impaired cellular immunity, either by in vitro testing with PHA or by vivo delayed hypersensitivity skin testing, indicating that impaired T-lymphocyte function is unlikely to be a common finding in all types of asbestos-associated malignancy.